2011
DOI: 10.1007/s11832-011-0374-y
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of compartment syndrome after flexible nailing of pediatric tibial shaft fractures

Abstract: Purpose Pediatric tibial shaft fractures are common injuries encountered by the orthopaedic surgeon. Flexible intramedullary nailing has become popular for pediatric patients with tibial shaft fractures that require operative fixation. The purpose of our study was to evaluate the incidence of, and the risk factors for, compartment syndrome (CS) after flexible intramedullary nailing of these injuries. Methods A retrospective review of tibial shaft fractures treated consecutively with flexible intramedullary nai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 39 publications
1
34
1
2
Order By: Relevance
“…Finally, a well-documented preoperative neurovascular examination is critical as preexisting neurovascular deficits in the absence of compartmental swelling may serve as an early warning sign of potential compartment syndrome after flexible nailing. 17 …”
Section: Physical Examinationmentioning
confidence: 99%
“…Finally, a well-documented preoperative neurovascular examination is critical as preexisting neurovascular deficits in the absence of compartmental swelling may serve as an early warning sign of potential compartment syndrome after flexible nailing. 17 …”
Section: Physical Examinationmentioning
confidence: 99%
“…However, it has been the authors' experience that older children with a closed tibial shaft fracture can be prone to delayed union and incomplete healing, which may lead to prolonged restrictions from activities and sports. Whereas flexible nail fixation has increased in popularity for the treatment of these fractures [2][3][4][5], significant complications such as compartment syndrome, malunion, nonunion, and nail migration have been reported [6,7], and casting currently remains the mainstay of treatment at most institutions [8]. The purpose of this study was to analyze success and failure of cast treatment for closed tibial diaphyseal fractures in the adolescent population.…”
Section: Introductionmentioning
confidence: 99%
“…This method may be similar to flexible intramedullary nailing of long bone fractures. In recent studies, [20,30] flexible intramedullary nailing of long bone fractures has been shown to have high risk for development of ACS in pediatric population. The reason may be soft-tissue trauma caused by multiple attempts to reduce the fracture and pass the nail.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it was reported in a recent study that ACS can also develop in pediatric tibial shaft fracture treated with flexible IMP. [20] Clinical observation has demonstrated that edema in tibial shaft fracture dissolves day after treatment with ICF; however there is no study investigating ICP measurements after application of ICF for tibial shaft fracture. ICP monitoring after IMP in such fracture has been well documented.…”
Section: Introductionmentioning
confidence: 99%